Involvement of Bcl-2 Activation and G1 Cell Cycle Arrest in Colon Cancer Cells Induced by Titanium Dioxide Nanoparticles Synthesized by Microwave-Assisted Hybrid Approach - Ranjan, Shivendu; Dasgupta, Nandita; Mishra, Debasish; Ramalingam, Chidambaram (Frontiers in Bioengineering and Biotechnology, 2020)
Toxic effect of TiO2 nanoparticles (TNP) greatly varies with the variation in synthesis protocol followed. Any morphological alteration of TNPs, affects its activity. In the present study, we report the detailed toxicological analysis of TNPs fabricated by microwave-irradiation assisted hybrid chemical approach. The toxicological mechanism was studied in human colon cancer cell lines (HCT116). Results indicated that TNP induces oxidative stress on HCT116 which causes mitochondrial membrane depolarization. We also observed activation of Bcl-2 and caspase-3 by western blot analysis. This indicates TNPs induces mitochondrial mediated apoptosis. Further, G1 cell cycle arrest was observed by flow cytometric analysis. This study provides an understanding into the mechanism of action for apoptosis induced by TNPs which can be further used to design the safety of TNPs for various consumer products and also suggests that extensive research need to be done on harmful effects of TNPs synthesized from different approaches before commercial application.